Onion (Allium cepa L.) peels: A review on bioactive compounds and biomedical activities - Kumar, Manoj; Barbhai, Mrunal D.; Hasan, Muzaffar; Punia, Sneh; Dhumal, Sangram; Radha; Rais, Nadeem; Chandran, Deepak; Pandiselvam, R.; Kothakota, Anjineyulu; Tomar, Maharishi; Satankar, Varsha; et al. (Biomedicine & pharmacotherapy, 2022)
Huge quantities of byproducts/wastes generated in onion processing are usually discarded, but they are excellent sources of bioactive compounds and phytochemicals. However, with growing interest in the sustainable use of resources and the circular economy to reduce adverse impacts on the environment, food processing wastes such as onion peel/skin can be extracted and employed as inputs in developing or reformulating nutrient supplements, and pharmacological drugs. This review highlights major bioactive components, especially total phenolics, total flavonoid, quercetin and its derivatives present in onion peel/skin and their therapeutic applications as cardioprotective, neuroprotective, antiobesity, antidiabetic, anticancer and antimicrobial agents. The present review emphasized that onion peel is one of the important agricultural by-products which is rich in bioactive compounds and can be utilized as health promoting ingredient especially in pharmacological and biomedical fields. Thus, with increasing burden of life style disorders/non-communicable diseases, finding suitable natural alternative for their treatment is one major concern of the researchers and onion peel and its extract can be exploited as a prime ingredient. •Exhaustive review considering extraction of onion peel bioactives and its characterization.•Bifunctionalities associated with onion peel extracts are discussed.•Bioactives exhibit antioxidant, antidiabetic, neuroprotective, and cardioprotective effects.•Onion peel have multifaceted application in fields of biomedicine and pharmaceuticals.